Special aspects of tissues regeneration in alveolar socket in diabetes patients - Барило, О. С.; Канішина, Т. М.; Закалата, Т. Р. (Actual Dentistry, 2019)
Resume. One of the main pathogenetic factors of slowed tissue regeneration in diabetes mellitus is the changes in the microcirculatory vessels that develop during the disease, and the slow and unregulated formation of new capillaries (angiogenesis). Angiogenesis is one of the physiological processes that plays a key role in the tissue's response to damage. Summary. Angiogenesis is among the most fundamental of physiological processes and is central to how tissues respond to injury. It is well established that an aberrant angiogenic response contributes to the pathogenesis of a number of diseases and can dramatically influence the course of wound healing. Purpose. With the help of morphological studies, to analyze the regenerative processes in the tissues of the alveolar sprout after tooth extraction in patients with diabetes mellitus, to evaluate the processes of physiological angiogenesis in the formation of granulation tissue. Materials and methods. In 20 patients with type 2 diabetes mellitus aged 40 to 60 years in both sexes, after the tooth was removed, a biopsy of the granulation tissue filling the tooth was performed 7 days after the tooth extraction. In 10 patients (who made the control group) after the tooth was removed, a blood clot was formed in the well. Healing of the well passed independently. The other 10 patients (they formed a test group) placed in the well PRF and fixed it with a p-like seam. Histological preparations were made by methods, staining of histological preparations with hematoxylin-eosin and on fibrin by Zerbyno D.D., Lukasevich L.L. (modified Martius-Scarlet Blue method). Microscopy and photographing of histological preparations were performed using an optical microscope OlympusBX41 with an increase of 40, 100, 200, 400 and 1000 times. Results. In the preparations of the experimental group, the number of newly formed capillaries and the number of endothelial cells is greater. In the preparations of the control group there is a small amount of smaller diameter of the newly formed vessels, therefore, the angiogenesis goes less active. This is confirmed by the results of morphometry. The diameter of vessels in the experimental group was 18.48±0.67 μm, their relative area – 14.8±0.51 %, in the control, respectively, 11.68±0.24 μm, and 9.04±0.21 %. In the microscopic study of granulation tissue revealed differences in its structure between the control and experimental groups. Conclusion. Structural and functional changes of the vessels of the microcircular bed are one of the most important factors that determine the slow healing of wounds in patients with diabetes mellitus. Thus, future therapeutic approaches to stimulation of angiogenesis, vascurriculation, targeted transportation of growth factors to the site of injury provide new opportunities for accelerating the healing of wounds (including post-extraction wounds) in patients with diabetes mellitus. Key words: diabetes mellitus, regeneration, tooth arch, angiogenesis, alveolar socket.